Efetividade e segurança da insulina em bolus versus em infusão contínua, no controle glicêmico de pacientes no pós operatório de transplante hepático - Fragoso, Luciana Vládia Carvalhêdo (2016)
Literature still presents controversy as to the best and safest method of glycemic control (intermittent or continuous) and target range in critically ill patients, comprising those who undergo liver transplantation. In the perspective of transplantation, this is an important subject given the deleterious effects of hyperglycemia and/or hypoglycemia on the patient and graft. In this context, this study aimed to analyze the effectiveness and safety of basal-bolus insulin therapy versus continuous insulin infusion in the glycemic control of patients in the immediate postoperative period of liver transplantation. It was a pragmatic, open-label, prospective clinical trial study conducted with 42 participants, divided into two groups (case and control), with 21 each, in the immediate postoperative period of liver transplantation. Participants in the case and control group received continuous insulin infusion and basal-bolus insulin therapy, respectively, from capillary glycaemia of 150mg/dl. Research Ethics Committee (CEP) of the Federal University of Ceará/PROPESQ approved the study under protocol No. 1,063,210. Furthermore, it was registered in the Brazilian Clinical Trials Registry (ReBEC), number RBR-9Y5tbp. There were no statistically significant differences from the time of glycemic reduction to the target range between the case and control groups among transplanted patients (p=0.919). About the presence of hypoglycemia (p=0.500) and the initial glycemic value (p=0.345), there were no statistically significant differences. Final value of glycaemia in the postoperative ICU was lower and statistically significant in the continuous infusion pump group in relation to the basal-bolus group (p<0.001). Additionally, the glycemic reduction variation was higher and statistically significant in the case group (p=0.041). Continuous infusion pump method achieved better results in reducing blood glucose values. The groups presented no differences regarding the time to reach the target range, hypoglycemia cases, and clinical outcomes. Based on the variation and final value of glycaemia, it was concluded that the continuous insulin infusion method was more effective in the glycemic control of patients in the postoperative period of liver transplantation.